Chair-side CAD/CAM fabrication of a single-retainer resin bonded fixed dental prosthesis: a case report - Carlos Alberto Jurado; Akimasa Tsujimoto; Hidehiko Watanabe; Jose Villalobos-Tinoco; Jorge Luis Garaicoa; Mark David Markham; Wayne Walter Barkmeier; Mark Andrew Latta (Restorative Dentistry & Endodontics, 2020)
This clinical report describes designing and fabricating a single-retainer resin-bonded fixed dental prosthesis with a chair-side computer-aided design/computer-aided manufacturing system. The whole procedure, from tooth extraction to final placement of the prosthesis, was completed in one day, and a single clinic visit. No clinical complications were found at the 2-year follow-up after placement of the restoration, and satisfactory functional and esthetic results were achieved.